2020
DOI: 10.1161/jaha.119.015372
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term (10‐Year) Outcomes of Stenting or Bypass Surgery for Left Main Coronary Artery Disease in Patients With and Without Diabetes Mellitus

Abstract: Background Data are still limited regarding whether there are differential long‐term outcomes after percutaneous coronary intervention versus coronary artery bypass grafting ( CABG ) for left main coronary artery disease with or without diabetes mellitus ( DM ). Methods and Results Using the 10‐year data from the MAIN ‐ COMPARE (Revascularization for Unprotected L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…On the basis of the inclusion and exclusion criteria, further eliminations were carried out: 293 articles were eliminated because they were based on a follow-up time period less than 10 years; 62 publications were meta-analyses, systematic reviews, or literature reviews; 21 articles were case studies; and 130 articles were duplicated studies. Finally, only eight studies [16][17][18][19][20][21][22][23] including three randomized trials and five observational cohorts were selected for this analysis as shown in Fig. 1.…”
Section: Search Outcomesmentioning
confidence: 99%
“…On the basis of the inclusion and exclusion criteria, further eliminations were carried out: 293 articles were eliminated because they were based on a follow-up time period less than 10 years; 62 publications were meta-analyses, systematic reviews, or literature reviews; 21 articles were case studies; and 130 articles were duplicated studies. Finally, only eight studies [16][17][18][19][20][21][22][23] including three randomized trials and five observational cohorts were selected for this analysis as shown in Fig. 1.…”
Section: Search Outcomesmentioning
confidence: 99%
“…Recent long‐term report from the MAIN‐COMPARE (Revascularization for Unprotected Left Main Coronary Artery Stenosis: Comparison of Percutaneous Coronary Angioplasty Versus Surgical Revascularization) registry reported that the clinical impact of DM favoring CABG over PCI has diminished over time from the bare‐metal stent to the DES. 19 Despite this, currently, no specific recommendations exist concerning the optimal revascularization strategy in patients with DM with LMCA disease. 10 …”
Section: Discussionmentioning
confidence: 99%
“…In LMSD, comparable adverse outcomes and mortality was observed in CABG and PTCA. 7,39 It could be argued that the above studies were underpowered as they did not utilise newer secondgeneration drug-eluting stent, Everolimus. NOBEL trial 40 and EXCEL trial 41 were two largest randomised trials that included Everolimus but they were not powered to study diabetic patients exclusively.…”
Section: Discussionmentioning
confidence: 99%